Креативщик: роман / А. Борисова - Борисова Анна (Борис Акунин: проект "Авторы", 2012)
Экземпляры: ф.15,ЦБ (20130628) / Инвентарный номер: 44544 / Цена: 303.27 / Авт.знак: Б 82 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6